The effect of trust, IT knowledge, and entrepreneur’s innovativeness to embrace or shun the internet of things - Abushakra, Ahmad; Nikbin, Davoud; Odeh, Ammar; Abdulwahab, Rasha (Frontiers in Psychology, 2022)
This study examines critical factors influencing Omani entrepreneurs’ adopting the Internet of Things (IoT) by expanding the constructs at the UTAUT2 (Unified Theory of Acceptance and Use of Technology) with entrepreneurs’ innovativeness, IT knowledge, and trust. A cross-sectional survey questionnaire was used to collect data from 158 entrepreneurs in Oman. Data were analyzed through the structural equation modeling technique using SmartPLS. The results indicated that performance expectancy (PE), Habit (HT), social influence (SI), trust (TR), IT knowledge (ITK), and entrepreneurs’ innovativeness (PI) significantly affect Omani entrepreneurs’ intention to adopt IoT. Nonetheless, the results show there is no significant relationship between hedonic motivation (HM), effort expectancy (EE), price value (PV), and facilitating conditions (FC) to adopt IoT. This study contributes to previous literature by incorporating entrepreneurs’ innovativeness, IT knowledge, and trust into UTAUT2. Furthermore, this study was conducted in a Middle Eastern country where there is strong support from the government for entrepreneurs; also, there is a gap of such studies in this area. This study helps practitioners in the field to get a better understanding of how to influence entrepreneurs, push them towards using IoT applications further and encourage non-users to start using them.